Design and thermal analysis on circular fin. (2020) - Senthilkumar, P.; Rajesh Babu, S.; Koodalingam, B.; Dharmaprabhakaran, T.
Abstract: As the amount of heat that needs to be removed from four stroke spark ignition engine constantly increases, thermal engineers are faced with never-ending challenges not only to Provide innovative thermal designs but also to push the limits of the available technology Finite element analysis (FEA) can also be useful in determining performance, especially conductivity gradients. The heat transfer coefficient can be determined using advanced FEA codes which incorporate fluid mechanics. These simplified terms represent a combination of several factors, such as material conductivity, lateral fin conduction, boundary layer formation, and effective surface area; however, pin fin geometry cannot easily be modeled by using either method. Each pin must be individually discredited, increasing the modeling time substantially. A simulation program will be developed for predicting and optimizing thermal performance of hi-directional a) circular fin Fins b) axial fins C) circular fins with triangular profile Comparative thermal tests will be carried out using Aluminum two stroke S.I engine made with circular fin, axial fins, and circular fins with triangular profile with varying material properties of engine block. The results of the circular fin will be also compared with those axial fins, and circular fins with triangular profile using finite element analysis program developed on Ansys software. In addition to the temperature measurements, the Thermal stress distribution will be investigated.